2005
DOI: 10.1061/(asce)1090-0241(2005)131:12(1552)
|View full text |Cite
|
Sign up to set email alerts
|

Ground Deformation Induced by Vacuum Consolidation

Abstract: The deformation characteristics of soil subjected to vacuum pressure are discussed and an approximate method is proposed for calculating settlement and lateral displacement of the ground induced by vacuum consolidation. Laboratory oedometer test results indicate that if the vacuum pressure alone is larger than the lateral stress required to maintain an at-rest ͑no horizontal strain͒ condition, there will be inward lateral displacement and the vacuum pressure will induce generally less settlement than a surchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(91 citation statements)
references
References 5 publications
4
83
1
3
Order By: Relevance
“…If only the vacuum pressure is larger than the lateral stress required for a no horizontal strain condition, an inward lateral displacement is observed. Based on a series of test results, Chai et al [1] reported an approximate method for calculating the ground lateral displacement induced by vacuum pressure.…”
Section: At the Boundary Of Treated Areamentioning
confidence: 99%
See 4 more Smart Citations
“…If only the vacuum pressure is larger than the lateral stress required for a no horizontal strain condition, an inward lateral displacement is observed. Based on a series of test results, Chai et al [1] reported an approximate method for calculating the ground lateral displacement induced by vacuum pressure.…”
Section: At the Boundary Of Treated Areamentioning
confidence: 99%
“…Table 2 lists the information needed to calculate the lateral displacement induced by vacuum consolidation by using the approximate method. Advances in Civil Engineering e method proposed by Chai et al [1] for calculating lateral displacement of the soil at the treated area boundary as a result of the vacuum-drain consolidation can be summarized as follows:…”
Section: At the Boundary Of Treated Areamentioning
confidence: 99%
See 3 more Smart Citations